Optimization of Instagram-Based Digital Marketing Strategies in Educational Institutions: A Case Study at SMP EDU Global School Bandung - Saif Abdulrahman Saif Nasr Alomari; Ana Yuliana Jasuni (Westscience Press, 2026)
The rapid development of digital technology has encouraged educational institutions to adopt digital marketing strategies to improve branding and attract prospective students. Social media platforms, particularly Instagram, have become important communication tools in educational marketing activities due to their wide reach and interactive features. However, maintaining audience engagement and delivering effective promotional content remain major challenges for many institutions. This study aims to analyze the implementation of Instagram-based digital marketing strategies at SMP EDU Global School Bandung and identify factors affecting audience engagement. This research employed a qualitative descriptive method with a case study approach. Data were collected through direct observation, participation during a 10-month internship program, documentation, and analysis of digital marketing activities conducted by the institution. The findings revealed that several challenges affected social media engagement, including inconsistent content planning, limited variation in content formats, and non-optimal posting schedules. To address these issues, improvements were implemented through the increased use of video-based content, storytelling strategies, more structured coordination, and audience-oriented content development. The study concludes that effective digital marketing in educational institutions requires strategic planning, creative content management, and continuous evaluation of audience behavior. Furthermore, integrating online and offline communication strategies contributes significantly to strengthening institutional branding and improving promotional effectiveness.